PENGARUH STARTER EXPERIMENT APPROACH TERHADAP HASIL BELAJAR FISIKA DI SMA/SMK KELAS X - Karlina Arti Suprapto (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
This study aimed to determine the effect of using the Starter Experiment Approach towards physics cognitive learning outcomes at SMA / SMK. This research will be held at SMA 105 Jakarta. The sample of this study is students in class X MIA A as an experimental class with 34 students and X MIA B as the control class with 32 students. The instrument consists of 25 multiple choice questions. Based on the analysis and t-test (hypothesis test) with a significance level of 5% and dk = 64, obtained ttable = 1.669 and tcalculate = 0.271 so Ho is accepted. The conclusion of this research, there is no significant influence between Starter Experiment Approach towards physics cognitiveÂ learning outcomesÂ at SMA / SMK on the material temperature and heat. Keywords: Starter Experiment Approach, Physics Learning Outcomes, Temperature and Heat